Konsep Dasar Pengembangan Tenaga Pendidik dan Tenaga Kependidikan - Agus Fauzi; Dace; Sri Marti Pramudena (STIT Fatahillah, 2024)
The study in this article aims to obtain basic concepts in the development of teaching staff and educational staff. This article also aims to find development models, development management, and principles for developing teaching and educational staff. Apart from that, this article also has the aim of finding an appropriate development process, identifying challenges to professionalism, and the role and function of LPTK in developing teaching staff and educational staff. This article was written using the literacy method, namely by reviewing various literature related to the specified theme. In this way, this method can be justified theoretically to obtain cognitive and theoretical dialectical results according to the predetermined theme. This article produces several basic concepts in the development of teaching staff and educational staff. This article also finds development models, development management, and development principles that are expected to improve the quality of teaching and educational staff. Apart from that, this article considers also an effective process in developing and identifying challenges to professionalism, the role and function of LPTK in developing teaching staff, and the education staff themselves.